Impact of the COVID-19 pandemic on alcohol or drug use symptoms and service need among youth: a cross-sectional sample from British Columbia, Canada - Kirsten Marchand; Guiping Liu; Emilie Mallia; Nikki Ow; Krista Glowacki; Katherine G. Hastings; Steve Mathias; Jason M. Sutherland; Skye Barbic (BMC, 2022)
Abstract Background Concerns about youth alcohol and drug use have risen since the declaration of the global COVID-19 pandemic due to the pandemic's impact on known risk and protective factors for substance use. However, the pandemic's immediate and long-term impact on youths' substance use patterns has been less clear. Thus, this study sought to determine how the COVID-19 pandemic impacted alcohol or drug use and its risk and protective factors among youth accessing integrated youth services. Methods We conducted a repeated cross-sectional study of patient-reported outcomes data collected between May 2018 and February 2022 among youth (n = 6022) ages 10-24 accessing a provincial network of integrated youth services in Canada. The main exposure of interest was the COVID-19 pandemic (March 2020 - February 2022) compared with a pre-pandemic period (May 2018 - February 2020). As measured by the Global Appraisal of Individual Needs - Short Screener, outcomes included the average number of past month alcohol or drug use symptoms and past month likelihood of service need for alcohol/drug use (moderate/high vs. low need). Interrupted time series (ITS) examined change in average monthly alcohol/drug use symptoms between the pre- and pandemic periods. Stratified multivariable logistic regression investigated how the pandemic modified the effects of established risk/protective factors on likelihood of alcohol/drug use service need. Results Fifty-percent of youth met the criteria for moderate/high likelihood of alcohol/drug use service need, with the odds being 2.39 times (95% confidence interval = 2.04, 2.80) greater during the pandemic compared to the pre-pandemic period. Results from the ITS indicated significant immediate effects of the pandemic on monthly substance use symptoms (p = 0.01). Significant risk/protective factors for service need included exposure to violence, engagement in meaningful activities, and self-rated physical and mental health; and the direction of their effects remained consistent across pandemic and pre-pandemic periods. Conclusions This study demonstrated that the COVID-19 pandemic corresponded with increased alcohol or drug use among youth accessing integrated services. This signals an urgent need for increased clinical capacity in existing youth services and policies that can respond to risk/protective factors for substance use earlier.